Pendampingan Sanggar Unggah-Ungguh Untuk Menjadi Paket Wisata Baru Dusun Sumberwatu - Bimantoro, M Rangga; Irfani, Achyar; Fatimah, Salma; Sadiya, Kana Ega; Ermaya, Ni Komang Angeli Sintawati Ayu; Afifi, Syahida Fatma; Shafira, Alisya Zeta; Maharani, Tuhu Ningtyas; Alghifari, Muhammad Hilmi; Widodo, Aris Slamet (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Sumberwatu Hamlet, located in Sambirejo Village, Prambanan Sub-district, Sleman Regency, has great potential in the tourism sector that provides economic benefits for the local community. However, in the midst of the rapid development of the times, social problems have emerged that are quite alarming, especially related to the decline in manners behavior in children aged 5-15 years. The lack of attention to ethics education, both in the family, school and community environment, is a factor that influences this condition. This community service activity aims to increase children's knowledge and awareness of manners through the establishment of Sanggar Unggah-Ungguh as an educational tourism destination in Sumberwatu Hamlet. The methods used in the implementation of this program include Focus Group Discussion (FGD) activities, the formation of the studio's organizational structure, the preparation of teaching materials, and training for studio trainers. FGDs were held four times a month, guided by resource persons. Training of trainers was held once and continued with two simulations of studio activities involving lecturers and students. The results of this activity show the high participation and enthusiasm of the Sumberwatu Hamlet community towards the establishment of the studio, as well as high concern for the issue of children's manners. This activity is expected to be a model for developing educational tourism based on local wisdom that is beneficial for the character building of the younger generation